Common Ends: Attempts toward the being of the artist - Araujo, Léa; Grando, Angela (Farol, 2025)
This article proposes an overview of issues related to the common in the arts, based mainly on the writing *The Society of the Artist: Activism, Death and Memory of Art* by Stéphane Huchet, 2023. Within this context, the article explores issues interconnected with artists-of-the-common and their specificities, such as motivations and strategies, traversing different temporalities and guided by critical thoughts and artistic praxis from different historicist moments in the arts. From a supposed end that can be rethought from the perspective of purposes, to the statutes that define being an artist, especially in contemporary times.